The effect of hypoxia on photocytotoxicity of TICS tricarbocyanine dye in vitro - Istomin, Y.P.; Alexandrova, E.N.; Zhavrid, E.A.; Voropay, E.S.; Samtsov, M.P.; Kaplevsky, K.N.; Lugovsky, A.P.; Lugovsky, A.А. (Experimental Oncology, 2006)
Aim: To evaluate the effect of cell oxygenation on photocytotoxicity of a novel tricarbocyanine indolenine dye covalently bound to glucose (TICS). Methods: HeLa cells were incubated with 5 µM TICS, 2 h later irradiated by laser at 740 nm with a light dose of 10 J/cm2, delivered at a power density of 10, 20, 25 or 30 mW/cm2, in air or in argon atmosphere, and then scored for viability. Results: The photocytotoxicity of TICS increased dramatically as the power density was reduced. Under hypoxia TICS-photosensitized cell death was determined but its value was lowered, compared to photoirradiation in the air. Conclusion: Photosensitizing effect of TICS is only partially dependent on the oxygenation of tumor cells. Цель: исследование влияния оксигенации клеток на фотоцитотоксичность нового трикарбоцианинового индоленинового красителя, ковалентно связанного с глюкозой (ТИКС). Методы: клетки HeLa инкубировали в среде, содержащей 5 мкМ ТИКС, а через 2 ч на воздухе или в атмосфере аргона облучили светом лазера с длиной волны 740 нм в дозе 10 Дж/см2 при плотности мощности 10, 20, 25 или 30 мВт/см2 . Затем была определена их жизнеспособность. Результаты: фотоцитотоксичность ТИКС значительно возрастала при уменьшении плотности мощности облучения. В условиях гипоксии гибель клеток, фотосенсибилизированная ТИКС, сохранялась, но несколько уменьшалась в сравнении с результатами фотооблучения на воздухе. Выводы: фотосенсибилизирующий эффект ТИКС только частично зависит от оксигенации опухолевых клеток.